Diversity, distribution and cultural significance of Coccinellidae (Ladybirds) in the Dehradun region of Uttarakhand, India - Jabbar Mir, Shafkat (Hacquetia, 2025)
This study assesses the diversity, distribution, and cultural significance of Coccinellidae (ladybirds) in Dehradun (India), documenting 32 species from 19 genera, with Coccinella as the predominant genus, including C. septempunctata, C. transversalis and Cheilomenes sexmaculata. Species richness was greatest at lower altitudes (300 m), with Coccinella septempunctata and Hippodamia variegatashowing a wide altitudinal distribution and a marked decrease with increasing altitude. Agricultural ecosystems harboured the greatest diversity of Coccinellidae, due to the availability of prey and habitat heterogeneity, while flower gardens, mango orchards and forests harboured fewer species. In particular, Illeis cincta, Halyzia sanscrita and Harmonia axyridis were frequently observed in both agricultural and floral habitats, reflecting their ecological adaptability. We studied also ethnozoological practices of Vann Gujjar and Pahari communities, who use species such as Coccinella hieroglyphica, C. leonina and Propylea dissecta to treat ailments such as asthma, cough and skin diseases. A cross-cultural analysis revealed different preferences between the species, with Coccinella septempunctata having the highest cultural value due to its symbolic and medicinal significance
Keywords: animal-assisted therapy; Coccinella; habitat (ecology); habitat (ekologija); India; Indija; kmetijska raba tal; land use, rural; terapija s pomočjo živali